TrilhEdu: Visualization of Educational Content Through Learning Trails Using Graphs and Gamification - Almeida, Gustavo R.; Garcés, Lina; Batista, Bruno G.; Silva, Elisa C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.244894, 2024)
Visualizing learning trails aims to present educational content that enhances understanding students' progress and needs. This process, however, encounters challenges related to complexity, quality, and consistency of content, as well as interpretation, personalization, and presentation of information in the context of a Pedagogical Course Project. This paper introduces TrilhEdu, a gamified web system that organizes content into learning trails visually represented by graphs. The system prioritizes students, enabling analysis of their progress and potential paths within a trail while allowing trail administrators to simulate and monitor student progress. User evaluations indicated that TrilhEdu provided a positive and motivating experience.